Unilateral Upper Molar Distalization In A Severe Case Of Class II Malocclusion. Case Presentation - Ioana Liliana Vâţă; Mariana Păcurar (Romanian Society of Oral Rehabilitation, 2013)
This presentation is uppon pacient C.C., female, age 9 years and 5 month, from Hârlău, Iași; initial appointment was în 2009 for esthetic imbalance. The chief complain of the pacient was the protrusion of anterior maxillary teeth. The diagnosis was skeletal class II, dental class II/1 Angle malocclusion, with crowding and no space for the eruption of second premolar due to the premature loss of decidous teeth, severe proclination of lower incisors, midline shift and increased overjet and overbite. For this severe case we used a class II mechanics based on the increasing upper arch lenght in the posterior region, using upper molar distalization combined in a second phase of treatment with four premolar extraction.